Job Satisfaction Mediates Training, Motivation, Digital Competence on Work Commitment at BPSDM Riau Island - Fendi Hidayat; Nurhatisyah Nurhatisyah; Naseha Elkarima; Angelina Eleonora Rumengan (Annals of Human Resource Management Research, 2026)
Purpose: This study investigates the influence of digital competence and work motivation on individual performance in digitalized organizational settings. Ongoing technological changes require employees to develop not only technical skills but also adaptive capabilities to respond effectively to dynamic work systems. Research Methodology: A quantitative explanatory approach was applied, involving respondents selected based on specific criteria. Data were collected through a structured questionnaire and analyzed using inferential statistical methods to assess the relationships among the variables. Results: The results revealed that digital competence significantly enhanced performance, particularly in improving efficiency and technology-based problem-solving. Work motivation plays a crucial role in strengthening employee engagement and goal attainment. Furthermore, the combined effect of both variables demonstrated a stronger contribution than their individual impacts. Conclusions: This study confirms the stronger role of personal resources in improving employee commitment in digitally transforming public institutions and supports the JD-R perspective regarding resource relevance. Limitations: This study's limitations include its cross-sectional design, potential omission of factors such as leadership style, and reliance on self-reported data, which may introduce bias despite attempts to mitigate it. Contributions: The findings provide empirical evidence for strategic human resource development and extend the JD-R theory in the public sector context.